Validation of the French Version of the Child Posttraumatic Stress Checklist in French School-Aged Children - Gindt, Morgane; Richez, Aurelien; Battista, Michèle; Fabre, Roxane; Thümmler, Susanne; Fernandez, Arnaud; Askenazy, Florence (Frontiers in Psychiatry, 2021)
Background: The Child Post-Traumatic Stress Disorder Checklist (CPC) updated to DSM-5 is a questionnaire aim to assess Post-Traumatic Stress Disorder (PTSD) symptoms in children. It is available in both parents and child versions. Back Translation Method has been used for the French translation of the CPC. It has not been yet validated in French-speaking populations. The aim of this study was to assess the psychometric properties and the validity of the CPC in a sample of French-speaking school-children and their parents. Methods: The sample was composed by 176 children outpatients implicated in the Nice terrorist attack (14th July 2016) aged 7 to 17 (mean= 11.68 years, SD = 2.63 months) and 122 parents. Cronbach’s alpha was used to test CPC internal consistency. Spearman-correlation coefficient was performed between the French version of the CPC and the Kiddie Schedule for Affective Disorders and Schizophrenia Present and Lifetime version (K-SADS-PL) to assess the convergent validity. A ROC curve was constructed to verify the validity of the cut-off scores. An evaluation of the sensitivity and specificity of each score and a comparison with the diagnosis of the K-SADS-PL were made. Finally, a principal components analysis with varimax rotation was computed to analyze the structure of the French version of the CPC. Results: Cronbach’s alpha coefficient was 0.90 for child version and 0.91 for parent version of the CPC. There was a statistical correlation between the K-SADS-PL for PTSD and the total score of CPC for the child version (r = .62; p<.001) and for the parent version (r = .55; p< .001). The sensitivity and specificity of the children version with a threshold of >20, were 73.1% and 84.7%, respectively, using the K-SADS-PL as the diagnostic reference for PTSD. Concerning the parent version, using the same recommended cut-off score, the sensitivity and specificity were 77% and 80.5%, respectively. Conclusions: The psychometric properties of the French CPC are good. This questionnaire appears to be valid and should be used in French-speaking children.